Hubungan Antara Kemampuan Berpikir Kritis Dengan Hasil Belajar Tematik Peserta Didik Kelas V Sekolah Dasar - Rizka Hardianti; Fidrayani Fidrayani (Elementar : Jurnal Pendidikan Dasar, 2022)
This study aims to determine the relationship between critical thinking skills and student learning outcomes, and to determine how much the level of critical thinking skills affects thematic learning outcomes. In this study using descriptive correlational method. The tools used to collect data were a Likert scale for critical thinking skills variables, and midterm exam results documents for learning outcomes variables. The sample used was a saturated sample, namely the entire population of 83 grade 5 students. The results showed that there was a significant positive relationship between critical thinking skills and learning outcomes, social studies, and civics. The coefficient of determination in this study was 6.4% for the relationship between critical thinking skills and Indonesian language learning outcomes, then for the relationship between critical thinking skills and social studies learning outcomes of 9.2%, and 6.7% on Civics learning outcomes. The influence of critical thinking skills on Indonesian language learning outcomes was 6.4%, social studies learning outcomes were 9.2% and civics learning outcomes were 6.7%, the rest were influenced by factors that were not thorough in this study.